Early Christianity in the Lycus Valley - Huttner, Ulrich (Ancient Judaism and early Christianity, 2013)
Introduction --Starting points --Sources and chronological framework --Questions : community formation and the search for a position --Historyof research --Fundamentals, surveys, conclusions --Epigraphy and archaeology --Archaeological perspectives --Theology --Geography and natural resources --Basic geography --Infrastructure --Agriculture and textile production --Building trades and technologies --Settlement geography I : Carura, Attouda, Trapezopolis, Tripolis --Settlement geography II : Laodicea, Hierapolis, Colossae --Historical background --Cultural and social background : identities and associations --Political background --Colossae in the "early period" --The Lycus Valley in the Hellenistic period : new foundations and political changes --Laodicea as a central city of the Roman province --Indigenous and Greek cults --Cults of Zeus --Cults of Apollo --The sanctuary of Lairbenos --Men --The mother of the Gods --The Hellenistic ruler cult --The Roman emperor cult --Jewish communities --Judaism in the Lycus Valley : the beginnings --Laodicea as a Jewish Center --Conflicts between Jews and Greeks --Symbiosis of Jews and Greeks in the Imperial Period --Pauline influence : Philemon and Colossians --Persons and networks --Paul's journeys in Asia minor --The prosopography of Philemon and Colossians --The network of churches and the Epistle to the Laodiceans --Nympha of Laodicea --First summary : social networks and Paul's authority --The Epistle to Philemon --Date --The social status of Onesimus --The religious service of Onesimus --Second summary : symbiosis of Christians and Pagans --The Epistle to the Colossians --The Pseudepigraphic problem of Colossians --Date --Addressee and author --Knowledge of Christ --The christological Hymn --The admonition against "philosophy" --Angel worship --Local color in the catalog of Vices --Renewal and liberation --Liturgical Hymns --The domestic code and stabilization of the social order --Mission through rhetoric --Third summary : the quest for a Christian position in Colossians --Summary regarding the Pauline Epistles --The letter in the apocalypse of John --Context --Historical Imponderables --Geographical setting.